Novel ex vivo disease model for extramammary Paget's disease using the cancer tissue-originated spheroid method. Issue 3 (September 2020) - Arita, Takahiro; Kondo, Jumpei; Kaneko, Yuka; Tsutsumi, Miho; Kanemaru, Mai; Matsui, Mari; Arakawa, Yukiyasu; Katoh, Norito; Inoue, Masahiro; Asai, Jun
Highlights: Effective EMPD treatments are lacking partly because of no current ex vivo models. We firstly established CTOSs, an ex vivo model of EMPD. CTOSs retain the characteristics of original tumors. CTOSs are useful for investigating the pathogenesis and treatments of EMPD. Abstract: Background: Extramammary Paget's disease (EMPD) is a rare skin cancer that frequently occurs in the anogenital region in the elderly. Prognosis in patients with metastatic EMPD is poor as EMPD treatment has advanced little in recent years, primarily because no EMPD cell line has been established. Objective: We aimed to establish an ex vivo EMPD disease model using the cancer tissue-originated spheroid (CTOS) method, which is used to prepare and culture primary cancer cells while maintaining cell–cell contact. Methods: Thirteen samples from 12 EMPD patients were obtained. CTOSs were prepared and cultured using CTOS method. Histopathological examination of the CTOSs was performed. We investigated optimum medium conditions and effects of growth factors for CTOS growth. Chemo-sensitivity assays were conducted. Results: CTOSs were successfully prepared from 3 primary lesions and 2 metastatic lymph nodes. Of these, 2 CTOSs (EMPD-3 and EMPD-4) could be maintained and passaged long term ex vivo . Following transplantation of CTOSs to NOD/Scid mice, CTOS-derived xenotumors exhibited ductal formation, indicating that CTOSs retained the original tumor characteristics. Chemo-sensitivity assays revealed that docetaxel significantly inhibited EMPD-3 growth in a dose-dependent manner, whereas EMPD-4 was not clearly inhibited. These findings indicate the heterogeneity of EMPD and potential use of chemosensitivity assays with patient-derived CTOS to select the most effective drugs for each patient. Conclusion: To our knowledge, this study represents the first establishment of an ex vivo -EMPD disease model involving conventional cell lines. EMPD CTOSs might be useful for developing new therapeutic strategies.